Association between metformin use and below-the-knee arterial calcification score in type 2 diabetic patients. Issue 1 (December 2017) - Mary, Aurélien; Hartemann, Agnes; Liabeuf, Sophie; Aubert, Carole; Kemel, Salim; Salem, Joe; Cluzel, Philippe; Lenglet, Aurélie; Massy, Ziad; Lalau, Jean-Daniel; Mentaverri, Romuald; Bourron, Olivier; et al.
Abstract Background Vascular calcification (VC) is common in type 2 diabetes, and is associated with cardiovascular complications. Recent preclinical data suggest that metformin inhibits VC both in vitro and in animal models. However, metformin's effects in patients with diabetic VC have not previously been characterized. The present study investigated the association between metformin use and lower-limb arterial calcification in patients with type 2 diabetes and high cardiovascular risk. Methods The DIACART cross-sectional cohort study included 198 patients with type 2 diabetes but without severe chronic kidney disease. Below-the-knee calcification scores were assessed by computed tomography and supplemented by colour duplex ultrasonography. Data on anti-diabetic drugs were carefully collected from the patients' medical records and during patient interviews. Biochemical and clinical data were studied as potential confounding factors. Results Metformin-treated patients had a significantly lower calcification score than metformin-free patients (mean ± standard deviation: 2033 ± 4514 and 4684 ± 9291, respectively; p = 0.01). A univariate analysis showed that metformin was associated with a significantly lower prevalence of severe below-the-knee arterial calcification (p = 0.02). VC was not significantly associated with the use of other antidiabetic drugs, including sulfonylureas, insulin, gliptin, and glucagon like peptide-1 analogues. A multivariate logistic regression analysis indicated that the association between metformin use and calcification score (odds ratio [95% confidence interval] = 0.33 [0.11–0.98]; p = 0.045) was independent of age, gender, tobacco use, renal function, previous cardiovascular disease, diabetes duration, neuropathy, retinopathy, HbA1c levels, and inflammation. Conclusions In patients with type 2 diabetes, metformin use was independently associated with a lower below-the-knee arterial calcification score. This association may contribute to metformin's well-known vascular protective effect. Further prospective investigations of metformin's potential ability to inhibit VC in patients with and without type 2 diabetes are now needed to confirm these results.